Clinical hemodynamic evaluation of patients implanted with a fully magnetically levitated left ventricular assist device (HeartMate 3) - Uriel, Nir; Adatya, Sirtaz; Malý, Jiří; Kruse, Eric; Rodgers, Daniel; Heatley, Gerald; Herman, Aleš; Sood, Poornima; Berliner, Dominik; Bauersachs, Johann; Haverich, Axel; Želízko, Michael; et al. (The Journal of heart and lung transplantation, 2017)
BACKGROUND: The HeartMate 3 (HM3) is a Conformiteé Européenne (CE) mark-approved left ventricular assist device (LVAD) with a fully magnetically levitated rotor with features consisting of a wide range of operational speeds, wide flow paths and an artificial pulse. We performed a hemodynamic and echocardiographic evaluation of patients implanted with the HM3 LVAD to assess the speed range for optimal hemodynamic support. METHODS: Sixteen HM3 patients underwent pump speed ramp tests with right heart catheterization (including central venous pressure [CVP], pulmonary artery pressure, pulmonary capillary wedge pressure [PCWP] and blood pressure [BP]) and 3-dimensional echocardiography (3DE). Data were recorded at up to 13 speed settings. Speed changes were in steps of 100 revolutions per minute (rpm), starting at 4,600 rpm and ramping up to 6,200 rpm. RESULTS: Mean original speed was 5,306 ± 148 rpm, with a majority of patients (10 of 16, 62.5%) having normal CVPs and PCWPs at their original rpm settings. Going from lowest to highest speeds, cardiac output improved at the rate of 0.08 ± 0.08 liter/min per 100 rpm (total change 1.25 ± 1.20 liters/min) and PCWP decreased at the rate of -0.48 ± 0.27 mm Hg per 100 rpm (total change -6.13 ± 3.72 mm Hg). CVP and systolic BP did not change significantly with changes in rpm. Left ventricular end-diastolic dimension (LVEDD) decreased at a rate of -0.15 ± 0.09 cm per 100 rpm. Number of rpm was adjusted based on test results to achieve CVPs and PCWPs as close to normal limits as possible, which was feasible in 13 (81.3%) patients. For the remaining 3 patients, medical management was pursued to optimize hemodynamic support. CONCLUSION: Hemodynamic normalization of pressures was achieved in the majority of patients implanted with the HM3 pump within a narrow speed range.
Keywords: senioři; left ventricular assist device; device optimization; design vybavení; hemodynamic evaluation; Male; Time Factors; mužské pohlaví; Prospective Studies; funkce levé komory srdeční; Equipment Design; ramp test; Follow-Up Studies; Magnetics; následné studie; ženské pohlaví; Humans; prospektivní studie; Hemodynamics; magnetismus; hemodynamika; časové faktory; srdeční selhání; Heart-Assist Devices; magnetic levitation; Female; Aged; Heart Failure; lidé; podpůrné srdeční systémy; Ventricular Function, Left